2022
DOI: 10.1155/2022/6975236
|View full text |Cite|
|
Sign up to set email alerts
|

A Retrospective Study of Effectiveness of Thoracoscopic Lobectomy and Segmentectomy in Patients with Early-Stage Non-Small-Cell Lung Cancer

Abstract: Background. Surgical treatment is the first choice for non-small-cell lung cancer. To date, there are only few studies on the changes in laboratory indexes in two types of surgery, namely, thoracoscopic lobectomy and segmental pneumonectomy. Aim. To investigate the clinical impact of thoracoscopic lobectomy and segmentectomy in patients with early-stage non-small-cell lung cancer. Methods. We retrospectively reviewed the medical records of 94 patients with early-stage NSCLC in our hospital from October 2017 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…26 In a retrospective study, it was found that lobectomy and segmental resection have similar clinical efficacy in the treatment of early NSCLC patients, 27 but segmental resection can maintain healthy lung tissue as much as possible, with less trauma, protect lung function, and promote postoperative recovery. 27,28 Several other population-based studies have found that lobectomy has a significant survival advantage over segmental resection. [29][30][31] With our results, lobectomy is more beneficial than segmental resection.…”
Section: Discussionmentioning
confidence: 99%
“…26 In a retrospective study, it was found that lobectomy and segmental resection have similar clinical efficacy in the treatment of early NSCLC patients, 27 but segmental resection can maintain healthy lung tissue as much as possible, with less trauma, protect lung function, and promote postoperative recovery. 27,28 Several other population-based studies have found that lobectomy has a significant survival advantage over segmental resection. [29][30][31] With our results, lobectomy is more beneficial than segmental resection.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer has a high incidence worldwide and is one of the leading causes of death among cancer patients [1][2] .Surgical resection remains the primary treatment for lung cancer patients, and lobectomy with regional lymph node dissection is widely accepted as the standard surgical procedure.This procedure aims to completely remove diseased tissues while preserving healthy lung tissues to effectively treat the disease [3][4][5] .It is a commonly used clinical treatment for lung cancer, known for its minimal invasiveness, reduced bleeding, and positive impact on postoperative recovery. However, patients' adherence to postoperative functional exercise can be in uenced by various factors [6] .…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…
This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:
…”
mentioning
confidence: 99%